Modular Termination for Second-Order Computation Rules and Application to Algebraic Effect Handlers - Hamana, Makoto (Logical methods in computer science, 2022)
We present a new modular proof method of termination for second-order computation, and report its implementation SOL. The proof method is useful for proving termination of higher-order foundational calculi. To establish the method, we use a variation of semantic labelling translation and Blanqui's General Schema: a syntactic criterion of strong normalisation. As an application, we apply this method to show termination of a variant of call-by-push-value calculus with algebraic effects and effect handlers. We also show that our tool SOL is effective to solve higher-order termination problems.